Voice abnormalities at school age in children born extremely preterm - French, N.; Kelly, R.; Vijayasekaran, S.; Reynolds, Victoria; Lipscombe, J.; Buckland, A.; Bailey, J.; Nathan, E.; Meldrum, S. (American Academy of Pediatrics, 2013)
Background and Objectives: Voice abnormality is a frequent finding in school age children born at <25 weeks’ gestation in Western Australia. The objective of this study was to determine the frequency of voice abnormality, voice-related quality of life, and demographic and intubation factors in this population. Methods: Survivors <25 weeks’ gestational age in Western Australia born from 1996 to 2004 were included. Voice assessments (auditory perceptual assessment scale and Pediatric Voice Handicap Index) were carried out by speech pathologists. Intubation history was obtained by retrospective chart review. Results: Of 251 NICU admissions, 154 (61%) survived. Exclusions were based on severe disability (11) or distant residence (13). Of 70 assessed, 67 completed assessments, 4 (6%) were in the normal range and 39 (58%) showed moderate-severe hoarseness. Simultaneous modeling of demographic and intubation characteristics showed an increased odds of moderate-severe voice disorder for children who had more than 5 intubations (odds ratio 6.96, 95% confidence interval 2.07–23.40, P = .002) and for girls relative to boys (odds ratio 3.46, 95% confidence interval 1.12–10.62, P = .030). Tube size and duration of intubation were not significant in the multivariable model. Median scores of parent-reported voice quality of life on the Pediatric Voice Handicap Index were markedly different for preterm (22) and term (3) groups, P < .001. Conclusions: Voice disorders in this population were much more frequent than expected. Further studies are required to assess voice across a broader range of gestational ages, and to investigate voice-protective strategies in infants requiring multiple episodes of intubation.